IDENTIFIKASI DAN ANALISIS IMPLEMENTASI SIKA DI PT. PERTAMINA EP PRABUMULIH - Nareshwari Nareshwari; Indriati Paskarini (The Indonesian Journal of Occupational Safety and Health, 2017)
Oil and gas industry have high hazard potential. Some of major hazard in the oil and gas industry are fire hazard, gas explosion, and gas poisoning. PT Pertamina EP Asset 2 Prabumulih Field have Safe Work Permit System (SIKA) to prevent potential hazard in workplace. This research aims to study the SIKA procedure and its implementation in PT Pertamina EP Asset 2 Prabumulih Field. This research is a qualitative study and conducted with cross sectional approach. Data used in the research are primary data and secondary data.  The result obtained from this research is PT Pertamina EP Asset 2 Prabumulih Field have multiple type of SIKA such as SIKA for hot operation, cold operation, digging, and confined space. SIKA form contained about the job description, location, amount of workers,inherent dangers, job requrements  such as Job Safety Analysis, personal protective equipment, fire extinguishers, ventilation, etc) and parties that responsible in the SIKA implementation. Implementation that have been observed compared and analyzed with current regulation  applied in PT. Pertamina EP Asset 2. Based on the result, implementation of SIKA has gone well.  SIKA have not well distributed across the field. Advice that can be given is the SIKA Document distributed in accordance with the relevant parties.Keywords : work permit,analysis, implementation